1996
DOI: 10.1002/chem.19960020807
|View full text |Cite
|
Sign up to set email alerts
|

Opening and Closure of the Fullerene Cage in cis‐Bisimino Adducts of C60: The Influence of the Addition Pattern and the Addend

Abstract: Abstract:The synthesis, isolation, and spectroscopic characterization of the bisimino[60]fullerenes C,,(NCOOR), (1 a: Moreover, it is shown that, by transforming cis-l-C60(NCOOtBu)2 (1 b) into cis-l-C6O(NH)2 (1 c), the fullerene cage can be closed in an intraring 2 n + 2 c j isomerization to valence isomer V. These are 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 45 publications
5
83
0
Order By: Relevance
“…The UV-vis spectrum (Fig. 1) of 1 in a toluene solution showed absorptions at 700, 630, 475, and 430 nm, which is very similar to that of a trans-2-bismethano- [60]fullerene product reported by Schick et al 9 The 1 H-NMR spectrum of 1 exhibited CH protons at 4.57 ppm as a singlet, CH 2 protons at 4.63 ppm as a quartet, and CH 3 protons at 1.64 ppm as a triplet. The 13 C-NMR spectrum (Fig.…”
Section: Resultssupporting
confidence: 73%
“…The UV-vis spectrum (Fig. 1) of 1 in a toluene solution showed absorptions at 700, 630, 475, and 430 nm, which is very similar to that of a trans-2-bismethano- [60]fullerene product reported by Schick et al 9 The 1 H-NMR spectrum of 1 exhibited CH protons at 4.57 ppm as a singlet, CH 2 protons at 4.63 ppm as a quartet, and CH 3 protons at 1.64 ppm as a triplet. The 13 C-NMR spectrum (Fig.…”
Section: Resultssupporting
confidence: 73%
“…[27] 15 is an exception to the rule that addition at the 6,6-junction forms the closed threemembered ring structure aziridinofullerene (or methanofullerene in the case of carbon addition). Upon conversion of the alkoxylcarbonyl group to the hydrogen atom, the closed isomer bisaziridinofullerene 16 was obtained.…”
Section: Nitrogen Insertion: Azahomofullerenesmentioning
confidence: 92%
“…[23] Several bisazahomofullerenes have been reported. [24][25][26][27] The two imino bridging groups are adjacent to each other in all three known type of structures. Bisazido compounds add to C 60 at two 5,6-junctions on the same hexagon to form bisazahomofullerene such as 13.…”
Section: Nitrogen Insertion: Azahomofullerenesmentioning
confidence: 99%
“…However, additions at the [6,6] junction of fullerenes mostly result in [6,6] closed adducts; [7] [6,6] open homofullerenes are stable only in special cases. [8][9][10] Hirsch et al [8] synthesized bis [6,6] homo[60]-fullerenes with a 1,2,3,4 addition pattern and found that the energy difference between the closed and open bis [6,6] isomers are rather small. [9] Taylor et al [10] reported a [6,6] open fluorooxahomofullerene derivative with oxygen bonded to fluorinated carbon atoms.…”
Section: Introductionmentioning
confidence: 99%